Insertion of large diameter through-thickness metallic pins in composites: dataset - Neale, Geoffrey; Skordos, Alexandros A. (Cranfield University, 2022)
Force vs Displacement Data.xlsx - Contains all the raw force versus displacement data for the insertion tests carried out in the associated publication.Thermal Ageing Analysis.xlsx - Contains the DSC data (time, temperature, rev heat capacity and rev heat flow) for Bx180-220 prepreg under ageing regimes in the associated publication.
Keywords: 'composite manufacture'; 'prepreg forming'; 'Through-thickness reinforcement'; 'pin insertion'; 'damage mechanics'; 'thermal ageing'; 'Manufacturing Processes and Technologies (excl. Textiles)'; 'Mechanical Engineering'; 'Materials Engineering not elsewhere classified'; 'Composite and Hybrid Materials'; 'Aerospace Materials'; 'Automotive Engineering Materials'